2021
DOI: 10.1186/s12933-020-01175-5
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin does not change cardiac index nor systemic vascular resistance but rapidly improves left ventricular filling pressure in patients with type 2 diabetes: a randomized controlled study

Abstract: Background In the EMPA-REG OUTCOME trial (Empagliflozin Cardiovascular Outcome Event Trial) treatment with the sodium-glucose cotransporter-2 (SGLT2) inhibitor empagliflozin significantly reduced heart failure hospitalization (HHF) in patients with type 2 diabetes mellitus (T2D) and established cardiovascular disease. The early separation of the HHF event curves within the first 3 months of the trial suggest that immediate hemodynamic effects may play a role. However, hitherto no data exist on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 29 publications
4
46
1
4
Order By: Relevance
“…Furthermore, Global Longitudinal Strain (GLS) determined by Speckle Tracking technique is a surrogate of left ventricular systolic function [ 15 ]. Clinical studies of the effects of SGLT2 inhibitors on myocardial deformation parameters are scarce [ 16 , 17 ]. Although LV longitudinal strain was previously measured by cardiac magnetic resonance [ 18 ], to our knowledge, there are no studies estimating GLS by speckle tracking echocardiography in patients treated with SGLT2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Global Longitudinal Strain (GLS) determined by Speckle Tracking technique is a surrogate of left ventricular systolic function [ 15 ]. Clinical studies of the effects of SGLT2 inhibitors on myocardial deformation parameters are scarce [ 16 , 17 ]. Although LV longitudinal strain was previously measured by cardiac magnetic resonance [ 18 ], to our knowledge, there are no studies estimating GLS by speckle tracking echocardiography in patients treated with SGLT2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In a placebo-controlled, randomized, double blind human trial (Figure 4A), 3 1,5-AG was significantly reduced by empagliflozin treatment , but not by placebo (Figure 4B). While at baseline (before empagliflozin), 1,5-AG showed a strong correlation to HbA1c and serum glucose, these correlations lost under conditions of empagliflozin treatment (Figure 4C,D).…”
Section: E T T E R T O E D I T O Rmentioning
confidence: 99%
“…2 A targeted analysis of 1,5-AG was performed in a placebo-controlled, randomized, double blind human trial with empagliflozin (n = 42). 3 We first explored serum metabolomics data of the MI cohort and Db/Db versus Db/+ mice (Figure 1A,B; Table S3 and Table S4). Considering the top 10 most significant metabolites by P-value, both data sets showed a clear separation of diabetes versus non-diabetes (Figure 1C,D; Tables S3 and S4).…”
Section: E T T E R T O E D I T O Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar beneficial effects on diastolic function in patients with type II diabetes mellitus were reproduced in smaller trials using empagliflozin or canagliflozin [ 129 , 130 ]. In another interesting randomized, double-blind, and placebo-controlled study Rau et al demonstrated that empagliflozin improved diastolic function (E/e´) as early as one day after initiation in diabetic patients, while non-invasively assessed hemodynamic parameters (stroke volume index, cardiac index, vascular resistance index or pulse rate) were unchanged [ 131 ]. While the results from two large clinical trials investigating the effects of empagliflozin (EMPEROR-Preserved [ 132 ]) or dapagliflozin (DELIVER [ 133 ]) in reducing cardiovascular death and heart failure events in non-diabetic patients with HFpEF are awaited for late 2021 and early 2022, respectively, there is pre-clinical evidence for an SGLT2i-mediated attenuation of diastolic dysfunction irrespective of a diabetic condition.…”
Section: Potential Role Of Reduced [Na + ] I For Cardioprotection By Sglt2imentioning
confidence: 99%